International Norms: The Impact of Women in Peace Building Processes - Akkoyun, Aişe Gül (Frontiers in Law, 2023)
This study points out that the rules of positive international law need to be more effectively enforced in practice. It explains the absence of women from peace processes as a result of a lack of effort to include them in official peace processes rather than women’s lack of experience in negotiation or conflict resolution. It emphasizes women as crucial agents in the transition from war to peace in order to promote social cohesion and political legitimacy. An excellent first step would be to use gender-sensitive language in a peace agreement and to create a platform for women to discuss the importance of including women in peace processes.